2013
DOI: 10.1186/1678-9199-19-14
|View full text |Cite
|
Sign up to set email alerts
|

Probable chronic renal failure caused by Lonomia caterpillar envenomation

Abstract: Erucism is a skin reaction to envenomation from certain poisonous caterpillar bristles. In Brazil, most reports of erucism provoked by Lonomia caterpillars are from the southern region. Most manifestations of erucism are local and include burning pain, itching, local hyperthermia and, rarely, blisters (benign symptoms with spontaneous regression in a few hours). General symptoms such as nausea and vomiting, headache, fever, myalgia, abdominal pain and conjunctivitis may also occur. Uncommon symptoms include ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…243,244,249 Development of CKD following Lonomia venom-associated AKI was described in 5 patients. 245,250 Loxosceles. Spiders of the genus Loxosceles are distributed worldwide, including SA and LA.…”
Section: Leptospirosismentioning
confidence: 99%
“…243,244,249 Development of CKD following Lonomia venom-associated AKI was described in 5 patients. 245,250 Loxosceles. Spiders of the genus Loxosceles are distributed worldwide, including SA and LA.…”
Section: Leptospirosismentioning
confidence: 99%
“…Envenomed victims display systemic hemorrhage secondary to intravascular disseminated coagulation [ for review see 1,2] . Frequently, the clinical profile evolves to acute kidney injury (AKI), which is the main cause of death following this type of envenomation [35] . In experimental models, L .…”
Section: Introductionmentioning
confidence: 99%
“…reported case of a patient whose Lonomia caterpillar sting went unrecognized until a week after the accident ended with progression to stage V chronic renal disease. 12 Recent research has focused on the specific mechanism of injury caused by Lonomia species. A study found that the venom of L obliqua causes cytoskeleton rearrangement and migration in vascular smooth muscle cells (VSMCs) by inducing formation of reactive oxygen species through activation of nicotinamide adenine dinucleotide phosphate oxidase.…”
Section: Wwwmdedgecom/dermatologymentioning
confidence: 99%